2014
DOI: 10.1007/s10577-014-9436-6
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of TTAGG-specific telomerase activity in insects

Abstract: In most eukaryotes, telomeres consist of tandem arrays of a short repetitive DNA sequence. Insect telomeres are generally constituted by a (TTAGG)n repeat motif. Usually, telomeres are maintained by telomerase, a specialized reverse transcriptase that adds this sequence to chromosome ends. We examined telomerase activity in 15 species across Insecta. Telomerase activity was revealed in Isoptera, Blattaria, Lepidoptera, Hymenoptera, Trichoptera, Coleoptera, and Sternorrhyncha. In contrast, we were not able to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 33 publications
1
40
1
Order By: Relevance
“…domestica ) revealed the TTAGG telomeric repeat in both those insects (Frydrychová et al, ). Nevertheless, real‐time quantitative telomeric repeat amplification protocol (RTQ‐TRAP) did not detect telomerase activity in L. saccharina (Korandová et al, ); however, the authors concluded that this failure could be explained either by a low amount of telomerase or by the presence of inhibitors of TRAP assays.…”
Section: Telomere Structure In the Class Insectamentioning
confidence: 99%
See 2 more Smart Citations
“…domestica ) revealed the TTAGG telomeric repeat in both those insects (Frydrychová et al, ). Nevertheless, real‐time quantitative telomeric repeat amplification protocol (RTQ‐TRAP) did not detect telomerase activity in L. saccharina (Korandová et al, ); however, the authors concluded that this failure could be explained either by a low amount of telomerase or by the presence of inhibitors of TRAP assays.…”
Section: Telomere Structure In the Class Insectamentioning
confidence: 99%
“…TTAGG‐specific telomerase activity was studied in a number of insect orders (Korandová, Krůček, Vrbová, & Frydrychová, ; Sasaki & Fujiwara, ). Distribution of this nucleotide sequence in insects is predominantly, but not universally, consistent with that of telomerase activity, and therefore suggests that the TTAGG‐telomerase system is functional in this group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example several insect groups do not exhibit this telomeric repeat, such as Diptera, Ephemeroptera, Odonata, Dermaptera, Siphonaptera, Mecoptera, Raphidioptera and parasitic Hymenoptera. In addition, Coleoptera, Neuroptera and Hemiptera orders include species with and without the ancestral (TTAGG) n telomeric motif (Frydrychová et al 2004, Gokhman et al 2014, Korandová et al 2014). In these insect groups, the ancestral telomeric motif is replaced by other alternative telomeric sequences such as (TCAGG) n in some coleopteran species (Mravinac et al 2011), non-(LTR)long terminal repeat retrotransposons in Drosophila Fallén, 1823 (Mason et al 2008), arrays of long satellite repeats in Culicomorpha dipteran (Walter et al 2001), or by unknown sequences as in damselflies, mayflies and some aphid species (Frydrychová et al 2004, Vítková et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Most insect orders and species possess telomerase, although they can vary in sequence of the RNA component (TERC) used as template for telomeric DNA (see ref. 26 and references therein). Drosophila elongates its telomeres by transposon addition, and mosquitoes and chironomids rely on gene conversion of terminal satellite sequences for telomere maintenance.…”
mentioning
confidence: 99%